Evolution of parasitemia in radical cure using qPCR for uncomplicated malaria by Plasmodium vivax in the Peruvian Amazon - Guzmán-Guzmán, Mitchel (2019)
Although there were a reduction in malaria burden, with 30% fewer cases in 2018 than in 2014, malaria remains a major public health problem in Peru, mainly in the Amazon region where over 44,000 cases were reported in 2018 (96% of cases in the country). Plasmodium vivax is the predominant species, representing 75.5% of malaria cases, similar to the rest of the region of the Americas. P. vivax infections are characterized by frequent relapses due to persistent liver dormant parasites. Previous studies of our research group in the Peruvian Amazon have shown high proportion of recurrence after radical cure (~75% in one year of follow-up [1]). This study aimed to describe the evolution of parasitemia after a supervised radical cure treatment in an endemic rural village in the Peruvian Amazon follow-up by both, molecular tools (qPCR) and thick smear, during one month.